A New Field in The Discipline of Nursing Forensic Nursing - Fırat, Sunay; Ünal, Sevi; Yalçın Geleş, Çiğdem (The Bulletin of Legal Medicine, 2016)
Health professionals generally lack adequate knowledge about the examination of victims and suspects, and the methods used for the identification, collection and preservation of legal evidence. In most forensic cases, nurses are the first persons in a medical team to see the victims or suspects, to contact their family or relatives, to handle their items and belongings during examination, and to collect laboratory samples. Forensic nursing is a new and gradually developing area of specialization that supports the judiciary through the knowledge and experiences associated with nursing. Forensic nurses contribute to the medical team by applying their basic nursing knowledge to the examination and scientific evaluation of victims and perpetrators in crimes involving violence, trauma and/or death. The aim of this study was to draw attention to forensic nursing as a new field of nursing; to review the current state of forensic nursing in Turkey and around the world; and to provide a general overview of its standards and areas of activity. Over the past 30 years, forensic nurses in medical teams around the world have been tasked with identifying and providing care for cases of injury, domestic violence and child abuse, and also with collecting evidence, guiding judicial processes as an impartial contributor, and responding to emergencies. After taking the necessary postgraduate trainings for professional development and improving their knowledge on standard nursing applications, nurses can provide patient care as forensic nurses while also supporting expert witnesses, defendants and court authorities in legal cases. Forensic nursing, which is relatively new discipline around the world, is also a new and developing field in Turkey. In Turkey, the job definition for forensic nurses has not yet been legally defined; consequently, most forensic cases are still examined by nurses with no special forensic training. For this reason, there is a requirement in Turkey for specialized forensic nurses with professional leadership and problem-solving skills, who can effectively apply holistic nursing approaches to forensic cases in accordance with national and international ethical requirements. Key Words: Forensic nursing; nursing; Forensic sciences; Turkey